<span>The general equation of a quadratic is expressed as y = ax^2+bx+c. To
convert the general equation to vertex form, we need to obtain this form:
(y- k)= a(x - h)^2
This could be done by using completing the square method.
</span><span>y = –3x^2 – 12x – 2
</span><span>y + 2 = –3(x^2 + 4x)
</span>y + 2 -12 <span>= –3(x^2 + 4x + 4)
</span>y - 10 = -3(x+2)^2
Therefore, the answer is the first option.
Answer: tan^2ø
(i’m gonna use ø as theta because i can’t find it)
explanation:
sin^2ø-1=cos^2ø because of one of the pythagorean identities
sin^2ø/cos^2ø is tan^2ø because sin/cos is tan- opposite/hypotenuse divided by adjacent/hypotenuse is opposite/adjacent
hope that helps- you can comment if you need any more explanation :)
P=2
Work:
<span><span><span>7p</span>−<span>(<span><span>3p</span>+4</span>)</span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span>7p</span>−<span>(<span><span>3p</span>+4</span>)</span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span>7p</span>+<span><span>−1</span><span>(<span><span>3p</span>+4</span>)</span></span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span>7p</span>+<span><span>−1</span><span>(<span>3p</span>)</span></span></span>+<span><span>(<span>−1</span>)</span><span>(4)</span></span></span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span>−<span>2<span>(<span><span>2p</span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span><span><span>(<span>−2</span>)</span><span>(<span>2p</span>)</span></span>+<span><span>(<span>−2</span>)</span><span>(<span>−1</span>)</span></span></span>+10</span></span><span><span><span><span><span><span>7p</span>+</span>−<span>3p</span></span>+</span>−4</span>=<span><span><span>−<span>4p</span></span>+2</span>+10</span></span><span><span><span>(<span><span>7p</span>+<span>−<span>3p</span></span></span>)</span>+<span>(<span>−4</span>)</span></span>=<span><span>(<span>−<span>4p</span></span>)</span>+<span>(<span>2+10</span>)</span></span></span><span><span><span>4p</span>+<span>−4</span></span>=<span><span>−<span>4p</span></span>+12</span></span><span><span><span>4p</span>−4</span>=<span><span>−<span>4p</span></span>+12</span></span><span><span><span><span>4p</span>−4</span>+<span>4p</span></span>=<span><span><span>−<span>4p</span></span>+12</span>+<span>4p</span></span></span><span><span><span>8p</span>−4</span>=12</span><span><span><span><span>8p</span>−4</span>+4</span>=<span>12+4</span></span><span><span>8p</span>=16</span><span><span><span><span><span>8p</span>8</span></span></span>=<span><span><span>168</span></span></span></span><span>p=<span>2
Hope this helps:)</span></span>
Answer:
The set of all points on a plane equidistant to a given point.